Regulation of RNA methylation linked to drug resistance in gastric cancer - Yang, Zihan; Ma, Yanpin; Xu, Ziyi; Liu, Hongyan; Gu, Xinyu; Sun, Jiachun (Frontiers in Cell and Developmental Biology, 2026)
In global terms, gastric cancer (GC) represents one of the most commonly occurring malignancies. It is positioned as the fifth most frequent cancer in terms of incidence and stands as the third primary contributor to cancer-related mortality. As per the latest global cancer report from 2020, there were approximately 1.1 million new cases of GC and about 800,000 new deaths in that year, making up 5.6% of new cases and 7.7% of deaths related to cancer. In recent years, as bioinformatics technology and high-throughput sequencing have advanced rapidly, our comprehension of the genetic and epigenetic alterations associated with GC has also progressed considerably. Among these alterations, RNA methylation, as one of the common modifications within RNA molecules, has been regarded as a key factor in the development and progression of GC. Research indicates that the dysregulation of RNA methylation influences GC development through various pathways. Therefore, understanding the pathogenic mechanisms of RNA methylation in GC is of great significance for the diagnosis, treatment and prognostic assessment of affected patients. In this review, we discuss various types of RNA methylation, including N6-methyladenosine (m6A), 5-methylcytosine (m5C), N7-methylguanosine (m7G), and N1-methyladenosine (m1A), and how they might affect the mechanism of GC. We also look at how RNA methylation impacts chemotherapy, targeted therapy, and immune resistance in gastric cancer, as well as the potential uses of RNA methylation in treating gastric cancer, setting the stage for more detailed research on RNA methylation in gastric cancer.